Outcomes and Therapeutic Management of Bladder Cancer - Moschini, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Bladder cancer is the second most common genitourinary malignancy, with 81,190 estimated new diagnoses in 2018, in the United States alone. Transurethral resection of the bladder and radical cystectomy with bilateral pelvic lymph node dissection constitute the standard treatment for non-muscle invasive or very high-risk non-muscle invasive bladder cancer, respectively. However, survival expectations have not shown to improve in the last 20 years, and new diagnostic and therapeutic tools are urgently needed to improve the outcomes of this potentially lethal disease.